Hydrothermal scheduling problem using evolutionary algorithms - Lim, Darren Wei Chin (2017)
This report presents the different variants of differential evolution algorithms like SHADE, L-SHADE, L-SHADE Sinusoidal and Local Search for solving the hydrothermal scheduling problem. In this dissertation, the most effective algorithm which is L-SHADE sinusoidal will be used to solve the hydrothermal scheduling with the consideration of nonlinearities like valve point loading of the thermal unit and prohibited operating zone of hydro units. The proposed algorithm has been tested on the multi-chain test system having four hydro units and one thermal unit. The experimental results are compared with the results reported in IEEE-Congress on Evolutionary Computation (CEC) 2011 competition problems who uses the genetic algorithm with a new Multi-Parent Crossover (MPC) and the implementation of the proposed algorithm is found effective.